An improved approach for the evaluation of the environmental impact of nano‐modified insulating oils in electrical transformers - Ioannis Chronis; Chao Tang; Constantinos S. Psomopoulos (IET Nanodielectrics)
Abstract Nano‐modified electrical insulating fluids are a promising new family of insulating oils with enhanced characteristics. They can significantly improve many properties, such as fire point, breakdown voltage, partial discharge inception voltage and thermal conductivity etc. However, nanoparticles have raised concerns about the possible harm to human health and the ecosystems, but the environmental impact of nano‐modified insulating oils is far more complicated than that. Following the recent research results on the stability of nano‐modified particles, the authors introduce environmental aspects that have not attracted attention so far, such as the possible loss of stability of the insulating oil, mechanical erosion problems in parts of the electrical transformer and problems in recycling processes that may turn waste nano‐modified insulating oils into an unwanted feed stock for recycling industries. An improved method for the environmental risk assessment (RA) of nano‐modified insulating oils, based on an existing model for the RA of nanoparticles, is proposed. The authors reflect the complicated nature of the nanoliquids, mainly due to the stability of the element, which seems to have a paramount role on their environmental impact and is neglected by the current approach in RA.